2011
DOI: 10.1029/2011gl047847
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater river diversions for marsh restoration in Louisiana: Twenty-six years of changing vegetative cover and marsh area

Abstract: The restoration of Louisiana's coastal wetlands will be one of the largest, most costly and longest environmental remediation projects undertaken. We use Landsat data to show that freshwater diversions, a major restoration strategy, have not increased vegetation and marsh coverage in three freshwater diversions operating for ∼19 years. Two analytic methods indicate no significant changes in either relative vegetation or overall marsh area from 1984 to 2005 in zones closest to diversion inlets. After Hurricanes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(50 citation statements)
references
References 26 publications
0
49
1
Order By: Relevance
“…To maintain the salinity gradient the diversions are continuous [12,13]. Despite careful planning and many years of operation, a recent study [14] found no significant changes in either relative vegetation or overall marsh area from 1984 to 2005 in zones closest to the diversion inlets. The lack of positive response to the freshwater diversions during this period has been attributed to inappropriate timing of discharge, insufficient discharge magnitude (need > 100 m 3 s −1 to induce sheet flow needed to carry sediment across the marsh at Caernarvon Diversion, while DPFD is too small and channelized to induce sheet flow [15], and/or overloading of nutrients affecting sediment stability [14,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To maintain the salinity gradient the diversions are continuous [12,13]. Despite careful planning and many years of operation, a recent study [14] found no significant changes in either relative vegetation or overall marsh area from 1984 to 2005 in zones closest to the diversion inlets. The lack of positive response to the freshwater diversions during this period has been attributed to inappropriate timing of discharge, insufficient discharge magnitude (need > 100 m 3 s −1 to induce sheet flow needed to carry sediment across the marsh at Caernarvon Diversion, while DPFD is too small and channelized to induce sheet flow [15], and/or overloading of nutrients affecting sediment stability [14,16].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of positive response to the freshwater diversions during this period has been attributed to inappropriate timing of discharge, insufficient discharge magnitude (need > 100 m 3 s −1 to induce sheet flow needed to carry sediment across the marsh at Caernarvon Diversion, while DPFD is too small and channelized to induce sheet flow [15], and/or overloading of nutrients affecting sediment stability [14,16]. After Hurricanes Katrina and Rita, in 2005, these areas sustained even larger losses in vegetation and overall marsh area, when compared to similar marshes of the adjacent reference sites [14,17]. The West Bay Sediment Diversion was designed for sediment capture.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is [26,27]. The negative impacts of hurricane and drought on Louisiana coastal wetlands and their NDVI are well documented [28][29][30]. Fluctuation in water levels due to tides and winds in coastal marshes can alter the NDVI values of the marshes [13][14][15].…”
Section: Oiling Effectsmentioning
confidence: 99%
“…Deegan et al (2012) increased the nitrate and phosphate concentration entering replicated salt marshes in Massachusetts and documented higher slumping of tidal creeks and horizontal shearing of the top 50 cm of marsh. Kearney et al (2011) attributed the loss of one-third of the coastal wetlands (-142 km 2 ) in an estuarine sub-watershed to the weakening of marsh soils when the area was exposed to nutrient-enriched Mississippi River water diverted into the area. These observations are consistent with Swarzenski et al's (2008) comparative analysis of ogliotrophic marshes receiving nutrient-rich Mississippi River water.…”
Section: Introductionmentioning
confidence: 99%